Pengaruh Motivasi Kerja, Lingkungan Kerja dan Disiplin Kerja Terhadap Produktivitas Kerja Karyawan di Pabrik Tahu Sari Klaten - Mahesa Birowo, Aldi; Fii Ahsani, Riska (PENG: Jurnal Ekonomi dan Manajemen, 2025)
The subject of this research is Sari Tofu Factory, located in Cokro Village, Tulung District, Klaten Regency. The factory has a production capacity of 3 tonnes of soybean per day, which is processed into various variants of tofu products. With this scale of production, the company employs 84 employees who work alternately for 24 hours to meet production needs. This study aims to empirically examine the influence of work motivation, work environment, and work discipline variables on employee productivity in a medium-scale manufacturing company engaged in tofu production. A quantitative approach was used in this study to obtain numerical data. The population in this study were 84 employees of Sari Tofu Factory. The sample in this study was 84 employees using saturated sample technique (Census Sample) where if the population is less than 100 then the number of samples taken as a whole. Data analysis in this study includes descriptive analysis to describe the characteristics of the data, as well as multiple linear regression analysis to test the research hypothesis. The t test, F test, and coefficient of determination are used to measure the significance of the influence of the independent variable on the dependent variable.